Penerapan Teknik Forward Chaining Dalam Meningkatkan Keterampilan Pra Menstruasi Anak Autis Inisial Amr Usia 11 Tahun Di Edufa Palembang - Ismiyanti; Umpu Malwa, Rosyidah; Graha Pratiwi, Rezky (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2024)
Premenstrual skills need to be taught to autistic children who already have secondary sexual development characteristics so that they can manage their own feminine care needs so that their independence is greater. This study aims to improve the premenstrual skills of autistic children with Forward Chaining Technique. The method used in this research is descriptive method with qualitative research type. Data collection is done through observation, interviews, and documentation. The research subject is an autistic child with the initials AMR who shows signs of secondary sexual development. The intervention program was conducted by therapists at Edufa Palembang using forward chaining techniques that were implemented consistently and intensively. The intervention involved prompting, positive reinforcement, and proper task analysis. The results showed a significant improvement in the mastery of premenstrual skills, especially in the ability to use sanitary napkins, before and after the intervention. This study emphasizes the importance of a systematic and intensive approach to improve autistic children's independence in managing their feminine care needs. There was an improvement in the mastery of the ability to use sanitary napkins between before and after the intervention was given.